Simulation modeling of electronic equipment sales - Pistunov, Igor (CPN Publishing Group, 2021)
Selected statistics on the implementation by a commercial firm of components such as microprocessors, printers and monitors that are part of personal computers. In order to prevent loss of profits in case of unsatisfactory demand, simulation was performed to determine the adequacy of stocks in the company's warehouses.
Keywords: мікропроцесор; реалізація моделювання; монітор; принтер